Diagnostic and correction of heterophoria - Drugović, Sonja (2017)
The presented master`s thesis describes the methods and principles of diagnostic and correction of heterophoria. In theoretical part I focus on metods examinating and measuring of heterophoria in optometry practice. There are show their possible solutions with prismatic correction. In practical part I meassuaring of heterophoria with using Madox teching and Von Grafee tests. The last chapter is focused on full correction of the measured heterophoria and treatment of heterophoria.